Case Report: Bowel obstruction caused by an adult fibrosarcoma located in the pelvis - Wang, Sixian; Liu, Yiming; Zhang, Jixin; Zhang, Junling; Wang, Xin (Frontiers in Surgery, 2025)
BackgroundAdult fibrosarcoma (FS) is a rare subtype of soft tissue sarcoma (STS). These tumors most commonly occur in the extremities and present as painless, enlarging masses; primary FS arising whin the abdominal cavity or pelvis represents an exceptionally uncommon entity, with limited documented cases.Case presentationWe report a case of primary pelvic adult FS in a 52-year-old male who presented with persistent abdominal pain and bowel obstruction. Abdominal Computed Tomography (CT) revealed a large, round, mixed-density mass occupying the pelvis, with suspected involvement of adjacent organs. Final histopathological diagnosis of adult FS was confirmed following comprehensive immunohistochemical workup.ConclusionThis case dramatically underscores the critical importance for gastrointestinal surgeons and oncologists to maintain awareness of rare STS like FS in patients presenting with unexplained abdominal symptoms or obstruction. Early recognition, facilitated by advanced imaging and meticulous pathology, and the multidisciplinary management strategy are paramount to optimizing outcomes in these diagnostically challenging and aggressive tumors.